Potential effect of hyaluronic acid and triamcinolone acetate, alone or combined, on chondrogenic differentiation of mesenchymal stem cells - Ocampo, Pablo E.; Vallejo, Viviana; Montoya, Luis M.; Rocha, Noeme S.; Landim, Fernanda da C.; Rahal, Sheila C. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Osteoarthritis is a complex degenerative disease with several factors contributing to joint damage. Objective: To compare the potential effect of hyaluronic acid (HA) and triamcinolone acetonide (TA), alone or combined, on the in vitro chondrogenic differentiation process of mesenchymal stem cells (MSCs). Methods: MSCs were divided into four groups: Control, HA, TA, and HA/TA combined. Each treatment group was cultured for 14 days in chondrogenic differentiation medium. The chondrogenic differentiation potential was assessed by histology and immunohistochemistry. Results: The HA and HA/TA-treated MSCs presented histological characteristics similar to native chondrocytes. The extracellular matrix (ECM) of TA-treated MSCs was compact and organized. Glycosaminoglycan staining was intense in Control, moderate in TA, slight in HA/TA, and undetectable in HA. Type II collagen immunoreactivity was high in the TA-treated ECM and MSCs. Conclusions: Histological analysis shows that HA influences morphological development similar to chondrocytes of the MSCs, but with low expression of specific cartilage molecules. The TA promotes formation of a compact and organized ECM.